2017
DOI: 10.1017/s0016756817000802
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the ultramafic rocks of the Tulu Dimtu Belt, western Ethiopia – do they represent remnants of the Mozambique Ocean?

Abstract: The East African Orogen contains a series of high-strain zones that formed as Gondwana amalgamated. The Tulu Dimtu shear belt is one of these N–S structures within the Barka–Tulu Dimtu zone in western Ethiopia, and contains ultramafic bodies of equivocal origin. Identifying the petrogenetic origin of these enigmatic rocks provides evidence for the geodynamic significance of these shear zones. Owing to their altered state, these ultramafic rocks’ well-preserved chrome spinels provide the only reliable evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 120 publications
(274 reference statements)
0
12
0
Order By: Relevance
“…The Saharan Metacraton is still very poorly known, but extensive late Mesoproterozoic subduction-related magmatism is found in Chad and west and north Sudan . To the west of this, in eastern Sudan and western Ethiopia magmatism associated with early Neoproterozoic subduction characterizes terranes that are thought to have formed over westward dipping subduction zones 44,49 . This longevity of subduction, which also includes that seen in the Sinai 36,37 , demonstrates that the EAO extends back into the Stenian, or even earlier, when terrane accretion and subduction-zone magmatism initiated against the Paleoproterozoic kernel of the 'metacraton'.…”
Section: The Western Margin Of the Eao (The Eastern Saharan Metacraton)mentioning
confidence: 99%
“…The Saharan Metacraton is still very poorly known, but extensive late Mesoproterozoic subduction-related magmatism is found in Chad and west and north Sudan . To the west of this, in eastern Sudan and western Ethiopia magmatism associated with early Neoproterozoic subduction characterizes terranes that are thought to have formed over westward dipping subduction zones 44,49 . This longevity of subduction, which also includes that seen in the Sinai 36,37 , demonstrates that the EAO extends back into the Stenian, or even earlier, when terrane accretion and subduction-zone magmatism initiated against the Paleoproterozoic kernel of the 'metacraton'.…”
Section: The Western Margin Of the Eao (The Eastern Saharan Metacraton)mentioning
confidence: 99%
“…Amalgamation of the Arabian-Nubian Shield (ANS) after Blades et al (2019bBlades et al ( , 2015, Armistead et al (2019) and Collins et al (submitted) and the incorporation of the ANS, Azania and TOAST into Gondwana along the East African Orogen at: (a) 800 Ma and (b) 520 Ma. Tan polygons are areas of continental lithosphere in the Neoproterozoic that we model, blue polygons are areas of present-day continental lithosphere that are inferred to exist during the Neoproterozoic, but without having firm geological evidence or that have been affected by subsequent deformation (e.g.…”
Section: Figure 17mentioning
confidence: 99%
“…PGM overgrowths and epitaxial growth (back-scattered electron images): (a) to (c) over-plating of erlichmanite over a resorbed surface, Guma Water, Freetown Peninsula, Sierra Leone, (reproduced from Bowles, 1986, with permission of the Society of Economic Geologists); (d) secondary colloform zonation and over-plating of erlichmanite Guma Water, Freetown Peninsula, Sierra Leone, Os-rich regions are lighter in colour, less Os-rich regions appear as tones of grey (redrawn from Hattori et al, 1991); (e) arborescent Pt-Pd grain, Pt-rich areas shown as white, Pd-rich areas in grey from Córrego Bom Sucesso, Minas Gerais, Brazil (reproduced from Cabral et al, 2007); (f) Os-Ir alloy platelets formed simultaneously with Pt-Fe alloy Guma Water, Freetown Peninsula, Sierra Leone (reproduced from Bowles, 1995, with permission of the BRGM); and (g) laurite epitaxial growth on isoferroplatinum showing the shared surface, Big Water, Freetown Peninsula, Sierra Leone (reproduced from Bowles et al, 2018a). Jackson, 2006), although the interpretation that Yubdo and other bodies lying along a common suture are ophiolitic remnants is also possible (Blades et al, 2019). The composition of chromite from fresh dunite lies mainly in the Alaskan-type field, although there is significant overlap into the ophiolite field, especially with samples of altered dunite (Fig.…”
Section: The Eluvial Regimementioning
confidence: 99%
“…Cousins and Kinlock (1976, using the name Birbir deposit) were correct to describe it as an eluvial deposit, although other reports describe it as alluvial. The Yubdo ultramafic body consists of a central core of dunite surrounded by a narrow peridotite with a larger outer rim of pyroxenite in the form that offers comparison with Alaskan-type intrusions (Belete et al , 2002; Jackson et al , 2005; Jackson, 2006), although the interpretation that Yubdo and other bodies lying along a common suture are ophiolitic remnants is also possible (Blades et al , 2019). The composition of chromite from fresh dunite lies mainly in the Alaskan-type field, although there is significant overlap into the ophiolite field, especially with samples of altered dunite (Fig.…”
Section: The Eluvial Regimementioning
confidence: 99%